TMI: Signaling Credible Claims in Crowdfunding Campaign Narratives. (December 2016) - Kim, Phillip H.; Buffart, Mickaël; Croidieu, Grégoire
One of the enduring insights about early-stage creative efforts is that their prospects for success depend on their ability to overcome a variety of liabilities of newness. In our study, we address one aspect of such liabilities: the ability to communicate credible claims about the merits of an idea when raising the funds required for execution. The narratives employed during fundraising are both a vehicle for assembling details about nascent ideas and a structure for communicating them to a wider audience. With this communication, entrepreneurs signal information that potential backers use to evaluate the claims. We argue that using language to differentiate new creative projects from the status quo is beneficial because of signal clarity, but employing a language of accountability that discloses too much information (TMI) may actually backfire when raising funds in open settings. We test this argument by analyzing a sample of crowdfunding campaign texts and find evidence supportive of our predictions. These results advance the literature on entrepreneurial narratives and signaling, establish some baseline characteristics of donation- and reward-based crowdfunding sites, and reinvigorate the application of Stinchcombe's arguments about the liabilities of newness within a contemporary context.